Glossophobia and Public Speaking Achievement among Indonesian EFL Undergraduate Students - Indahsari, Mayumi Omita; Rahmawati, Eri; Baihaqi, Akhmad (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2025)
The background of this research was based on students’ problems in overcoming glossophobia, which affects their confidence, English proficiency, and performance in public speaking activities, ultimately impacting their academic achievement. The objective of this research is to find out whether there is a correlation between glossophobia and public speaking achievement among second semester students. This research used correlational method. The population of this research was second semester students of English Department at one public university in Banten Province, Indonesia. This study used cluster random sampling. There were 40 students as sample of this research. The data of this research was collected by giving glossophobia questionnaire and collecting public speaking scores. Based on the students’ glossophobia and public speaking achievement, the value of coefficient correlation test was -0.317 which means values close to zero indicate the correlation was low. The correlation was statistically significant with a significance of 0.047. Therefore the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. The findings indicate an inverse relationship between glossophobia and public speaking achievement, suggesting that as glossophobia increases, public speaking achievement decreases, and vice versa.